Experimental and numerical analysis of blast response of High Strength Fiber Reinforced Concrete slabs. (15th November 2018) - Luccioni, B.; Isla, F.; Codina, R.; Ambrosini, D.; Zerbino, R.; Giaccio, G.; Torrijos, M.C.
Highlights: Results of blast tests on High Strength Fiber Reinforced Concrete slabs are presented. Blast response of High Strength Fiber Reinforced Concrete is numerically analyzed. Effect of fiber length and content on response under close-in explosions is studied. Shorter fibers are more effective controlling cratering and spalling. Abstract: High Strength Fiber Reinforced Concrete (HSFRC) presents great advantages when compared with conventional concrete under static loads and thus, it constitutes a promising material to withstand extreme loads. The experimental results of blast tests performed on HSFRC slabs including different types of hooked end steel fibers are presented and numerically analyzed in this paper. The numerical simulation was able to reproduce the experimental results and it confirms that for the same fiber content, shorter fibers provide greater blast resistance, showing smaller craters and spalling at the back face.